2018
DOI: 10.1177/1055665618758686
|View full text |Cite
|
Sign up to set email alerts
|

Otologic Outcomes With Two Different Surgical Protocols in Patients With a Cleft Palate

Abstract: Early Sommerlad intravelar veloplasty may reduce persistent OME and consequently the need for ventilation tubes insertion, compared to later Veau-Wardill-Kilner palatoplasty.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(16 citation statements)
references
References 34 publications
2
13
1
Order By: Relevance
“…The number of participants who had grommets inserted (41%) is high compared with 18.9% reported by Gani et al (2012), but similar to the 39.3% reported by D’Andrea et al (2018) after the Sommerlad technique and 45.5% reported on national UK data by Fitzsimons et al (2017). The high numbers of grommet insertion reported in this study reflects historical practice.…”
Section: Discussionsupporting
confidence: 77%
“…The number of participants who had grommets inserted (41%) is high compared with 18.9% reported by Gani et al (2012), but similar to the 39.3% reported by D’Andrea et al (2018) after the Sommerlad technique and 45.5% reported on national UK data by Fitzsimons et al (2017). The high numbers of grommet insertion reported in this study reflects historical practice.…”
Section: Discussionsupporting
confidence: 77%
“…Similarly, other studies corroborated that palatal muscle reconstruction and relocation decrease the rate of eustachian tube dysfunction [16,17]. Brgoch et al and D'Andréa et al emphasized the role of Sommerlad IVVP in reducing the incidence need of ventilation tube placement [11,18]. On the contrary, Mantilla et al suggested the combination of palatoplasty and ventilation tube insertion.…”
Section: Discussionmentioning
confidence: 89%
“…It shows that the applied method performed significantly in the improvement of the middle ear effusion. Several studies approved the effect of palatoplasty in reducing the incidence of OME, while they did not find any statistically significant correlation between the surgical technique and the reducing impact on middle ear effusion [11][12][13][14]. On the other hand, Hassan et al reported that Sommerlad IVVP was associated considerably with a lower incidence of OME in comparison with the (Veau-Wardill-Kilner) VWK palatoplasty [15].…”
Section: Discussionmentioning
confidence: 99%
“…It shows that the applied method performed significantly in the improvement of the middle ear effusion. Several studies approved the effect of palatoplasty in reducing the incidence of OME, while they did not find any statistically significant correlation between the surgical technique and the reducing impact on middle ear effusion [ 11 14 ]. On the other hand, Hassan et al reported that Sommerlad IVVP was associated considerably with a lower incidence of OME in comparison with the (Veau-Wardill-Kilner) VWK palatoplasty [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, other studies corroborated that palatal muscle reconstruction and relocation decrease the rate of eustachian tube dysfunction [ 16 , 17 ]. Brgoch et al and D’Andréa et al emphasized the role of Sommerlad IVVP in reducing the incidence need of ventilation tube placement [ 11 , 18 ].…”
Section: Discussionmentioning
confidence: 99%